A Mathematical Model of Industrial Waste-Derived Fuel Droplet Combustion in High-Temperature Air - Dmitrii Antonov; Dmitrii Glushkov; Kristina Paushkina; Daria Kuznechenkova; Anand Ramanathan (Applied Sciences, 2022)
The results of a theoretical and experimental study of the processes of ignition and combustion of a single composite liquid fuel (CLF) droplet based on wet coal processing waste and combustible municipal solid waste under radiant and convective heating are presented. Based on the results of a detailed analysis of video recordings and previously obtained experimental data from the ignition and combustion of a single CLF droplet, a mathematical model was developed. The advantage of the developed mathematical model lies in the specification of sequential physical and chemical processes of the high-temperature decomposition of fuel in a high-temperature gaseous medium. A numerical simulation of combustion characteristics was carried out in the Ansys Fluent commercial software for five different CLF compositions. The ignition-delay times were established for fuel droplets that were in a preheated motionless air environment, a temperature in the range of 723–1273 K, and an air flow heated to 723–973 K moving at a velocity of 3 m/s. Using the asymptotic procedure, satisfactory analytical solutions are obtained for the multistage nonlinear problem of ignition and combustion of a single CLF droplet. The possibility for the practical application of the developed program in Ansys Fluent in predicting the characteristics of the ignition processes of CLF droplets is substantiated.